1D N-doped hierarchically porous hollow carbon tubes derived from a supramolecular template as metal-free electrocatalysts for a highly efficient oxygen reduction reaction. Issue 15 (28th March 2018) - Zhao, Lei; Sui, Xu-Lei; Zhou, Qing-Yan; Li, Jia-Zhan; Zhang, Jing-Jia; Huang, Guo-Sheng; Wang, Zhen-Bo
Abstract : 1D hollow nitrogen-doped carbon tubes (h-NCTs) were fabricated through a supramolecular template-derived approach and employed as the structure-guiding template, porogen and nitrogen source for in situ N-doping. Abstract : For the first time, a supramolecular template-derived synthesis approach is reported to fabricate 1D nitrogen-doped hollow carbon tubes (h-NCTs) with a hierarchical micro/mesoporous structure. A melamine cyanurate supramolecular assembly is used as the tubular-structure guiding template and nitrogen source, endowing the obtained h-NCTs catalyst with proliferative catalytic active sites, a high surface area as well as a well-defined multiscale pore system. The sample prepared at 900 °C (h-NCT-900) displays an exceptional half-wave potential of 0.86 V versus RHE, which is one of the best values recorded in the literature for a metal-free electrocatalyst.